2014
DOI: 10.3389/fmicb.2014.00279
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MreB interactors in Chlamydia reveals a RodZ homolog but fails to detect an interaction with MraY

Abstract: Chlamydia is an obligate intracellular bacterial pathogen that has significantly reduced its genome in adapting to the intracellular environment. One class of genes for which the bacterium has few annotated examples is cell division, and Chlamydia lacks FtsZ, a central coordinator of the division apparatus. We have previously implicated MreB as a potential substitute for FtsZ in Chlamydia (Ouellette et al., 2012). Thus, to identify new chlamydial cell division components, we searched for proteins that interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 32 publications
(68 reference statements)
4
45
0
Order By: Relevance
“…Thus, important modifications of division mode due to the lack of RodZ are expected. This is in agreement with the fact that the chlamydial RodZ is truncated, lacking its C-terminal periplasmic domain, and cannot complement an E. coli RodZ mutant (Ouellette et al, 2014). …”
Section: Introductionsupporting
confidence: 84%
“…Thus, important modifications of division mode due to the lack of RodZ are expected. This is in agreement with the fact that the chlamydial RodZ is truncated, lacking its C-terminal periplasmic domain, and cannot complement an E. coli RodZ mutant (Ouellette et al, 2014). …”
Section: Introductionsupporting
confidence: 84%
“…Furthermore, rod‐shaped morphology of rodZ deficient E. coli was partially restored with complementation of CT009 supporting structural observations and providing evidence that CT009 functions as a homolog to RodZ. Bacterial two‐hybrid analyses demonstrated interaction with the key morphogenic protein MreB, similar to previous report (Ouellette et al ., ). Mutagenesis of two amino acids in CT009 that are predicted to be central to interactions with MreB provided additional level of specificity for these interactions.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, sequence similarity searches reveal that this protein contains a predicted helix‐turn‐helix motif within a conserved xenobiotic response element (XRE) domain superfamily of DNA‐binding transcription factors. However, a recent study (Ouellette et al ., ) using bacterial two‐hybrid analysis indicated that CT009 interacts with MreB and supported a potential role as RodZ homolog. As described herein, in‐depth computational and experimental protein structural analyses were performed to provide more comprehensive support for CT009 as a RodZ homolog.…”
Section: Introductionmentioning
confidence: 98%
“…Second, using a new technique that is based on the incorporation of click-chemistry-modified d -amino acid probes, newly assembled peptidoglycan was visualized at the septum of dividing reticulate bodies in a ring-like structure, which indicated that peptidoglycan may have a role in cell division 170 . Third, MreB, an actin homologue, was found to localize at the septum in a manner that was dependent on peptidoglycan precursors and its conserved regulator RodZ (also known as CT009) 171173 , where it is thought to functionally compensate for the lack of FtsZ. Fourth, muramyl peptides and larger muropeptide fragments in Chlamydia trachomatis were isolated from fractionated infected cell lysates using a NOD-activated reporter cell line as a sensitive read-out 174 .…”
Section: Figurementioning
confidence: 99%